Quantum Computing: Exploiting a Single‐Crystal Environment to Minimize the Charge Noise on Qubits in Silicon (Adv. Mater. 40/2020). Issue 40 (7th October 2020) - Kranz, Ludwik; Gorman, Samuel Keith; Thorgrimsson, Brandur; He, Yu; Keith, Daniel; Keizer, Joris Gerhard; Simmons, Michelle Yvonne
Abstract : Atom qubits in silicon provide a promising platform for realising a scalable quantum computer. In article number 2003361, Michelle Simmons and co‐workers present a qubit environment with a notably low level of charge noise achieved by hosting phosphorus atoms in an all‐crystalline silicon substrate well‐separated from surface and interface states. The level of charge noise experienced by the phosphorus atoms is sufficiently low to enable two‐qubit gate fidelities above 99.99%, well within the 99% threshold required for error‐correction.